Das "Jüdisch-Mittelalterliche Erbe in Erfurt" auf der Welterbeliste - Stürzebecher, Maria (Aschkenas, 2024)
On September 17, 2023, the Jewish Medieval Heritage in Erfurt was inscribed on the UNESCO World Heritage List at the 45th session of the World Heritage Committee chaired by Saudi Arabia in Riyadh. This brought a decades-long process to its provisional conclusion, in which research into the history of the Jewish community in Erfurt in the Middle Ages and its material evidence had been intensified in preparation for the World Heritage application and also during the evaluation, thus leading to a great increase in knowledge. This process should and must continue, but an (interim) conclusion can be drawn in this paper.